Perceptions of Process Quality in Building Projects - Arditi, David; Günaydın, Hüsnü Murat; Günaydın, Hüsnü Murat (American Society of Civil Engineers (ASCE), 1999)
A Delphi process and a questionnaire survey are conducted to investigate the differences in the perceptions of entry-level professionals and long-time practitioners with regard to process quality in building projects. The factors that affect process quality in the three phases (design, construction, and operation) of a building project's life cycle are identified and ranked by the respondents' perceived degree of importance. The findings indicate that the perceptions of entry-level professionals and long-time practitioners are in agreement for most (74%) of the factors. Given the differences in the respondents' background, expectations, and experience, differences in perceptions are to be expected in the remaining 26% of the factors. Analyzing these differences helps in revising and improving existing training courses and academic programs. It is recommended that college programs include courses that treat the administrative aspects involved in the building project in great detail and that continuing education programs cover quality training and life cycle cost analysis.
Keywords: Project management; Buildings; Construction industry; Engineering education; PERT; Professional aspects; Quality assurance